Дорвыжы: удмурт батырлыко эпос / Михаил Худяков - Худяков Михаил Георгиевич (Удмуртия, 2008)
Экземпляры: Ч/з (20081124) / Инвентарный номер: 92879 / Цена: 100.00 / Авт.знак: Х 98 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)